Cyclic Fatigue Resistance of Nickel–Titanium Rotary Instruments after Simulated Clinical Use - Hana R. Ubaed; Diyar Kh. Bakr (Applied Bionics and Biomechanics)
Objective. Cyclic fatigue occurred in the curved canal when the instrument freely rotated leading to repeated compressive and tensile stresses. This study aims to evaluate the cyclic fatigue resistance (CFR) of new and used 2Shape and AF F-One rotary instrument systems by using an artificial stainless-steel canal. Methods. A total of 80 rotary nickel–titanium (NiTi) instruments of two systems were used, 2Shape/TS2 and AF F-ONE/F5 (40 in each group). The instruments were subdivided into group A 20 instruments (10 per system) that remain unused, group B 20 instruments (10 per system) instrumented 20 root canals (each file prepared 1 canal for 2 minutes), group C 20 instruments (10 per system) instrumented 40 canals each for 2 minutes (each file prepared 2 canals), group D of 20 instruments (10 per system) prepared 60 canals each for 2 minutes (each file prepared 3 canals). After each canal instrumentation, the instruments were cleaned and sterilized by autoclave. Then, all the instruments underwent cyclic fatigue testing in an artificial stainless steel canal with a 50° canal curvature and a radius of curvature of 5 mm. The time and number of cycles to failure (NCF) were recorded. Data were analyzed using the Welch ANOVA test for intragroup comparison and the pairwise test for multiple comparisons. Results. The unused instruments of the AF F-One rotary system showed statistically higher CFR than clinically used instruments (P<0.05). 2Shape system was not affected by clinical use (P>0.05). The mean NCF of AF F-One instruments was significantly higher than the equivalent file group of 2Shape instruments (P<0.05). Conclusion. A reduction in the CFR for AF F-One instruments after use was observed when compared to the new unused file group. The 2Shape system was not affected by clinical use. AF F-One performed better in terms of NCF.